2020
DOI: 10.1002/ejoc.202000870
|View full text |Cite
|
Sign up to set email alerts
|

Electron‐Withdrawing Substituted Quinazoline Push‐Pull Chromophores: Synthesis, Electrochemical, Photophysical and Second‐Order Nonlinear Optical Properties

Abstract: A series of chromophores bearing 4‐cyanoquinazoline, 2‐(4‐cyanophenyl)quinazoline or 2‐(4‐trifluorophenyl)quinazoline electron–acceptor (A) and 5‐(4‐aminophenyl)thiophen‐2‐yl or 4‐aminophenyl electron‐donor (D) units has been designed. The influence of the electron‐withdrawing substituent on the pyrimidine core as well as the nature of the amino electron donating group has been studied by cyclic voltammetry, UV/Vis and emission spectroscopy. Whereas 2‐(4‐cyanophenyl)quinazoline and 2‐(4‐trifluorophenyl)quinazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 71 publications
1
16
0
Order By: Relevance
“…Incorporation of 4-cyanoquinazoline or quinazolin-4(3 H )-one cores allows to reinforce the electron-withdrawing properties. We described synthesis and photophysical properties of 4-cyano-2-thienylquinazoline derivatives [ 31 ], and we confirmed the strong electron withdrawing nature of 4-cyanoquinazoline core. On the other hand, quinazolin-4(3 H )-one bearing 5-(4-diethylaminophenyl)thiophen-2-yl substituent at the position 2 possesses strong photoluminescence in the solution [ 32 ].…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations
“…Incorporation of 4-cyanoquinazoline or quinazolin-4(3 H )-one cores allows to reinforce the electron-withdrawing properties. We described synthesis and photophysical properties of 4-cyano-2-thienylquinazoline derivatives [ 31 ], and we confirmed the strong electron withdrawing nature of 4-cyanoquinazoline core. On the other hand, quinazolin-4(3 H )-one bearing 5-(4-diethylaminophenyl)thiophen-2-yl substituent at the position 2 possesses strong photoluminescence in the solution [ 32 ].…”
Section: Introductionmentioning
confidence: 76%
“…Synthetic approach to 4-cyano-2-thienylquinazolines 7 was developed by our research group earlier [ 31 , 32 ]. It includes nucleophilic substitution of chorine atom at position 4 of quinazoline core by the CN group in DMF under heating and subsequent Suzuki-Miyaura cross-coupling with arylboronic acid.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[28] Quinazoline chromophores have only been studied in recent years and their push-pull derivatives have mainly been based on quinazolin-2-yl and quinazolin-4-yl fragments. [35,[38][39][40][41][42][43] In particular, some of us have described a set of amino-substituted aryl-, styryl-, and arylethynylquinazolines. [44] It was found that all of these compounds exhibit emission quenching upon protonation.…”
Section: Introductionmentioning
confidence: 99%